Belajar Matematika Gampang Asyik dan Menyenangkan Bersama Siswa SMK di Perbatasan Timor Leste - Lakapu, Meryani; jagom, yohanes ovaritus; Fernandez, Aloysius Joakim; Ola, Stefanus; Molo, Matilde Niis; Djong, Kristoforus Djawa; Uskono, Irmina Veronika; Gawa, Maria Gracia Manoe; Nai, Yustinus Didimus (Prioritas: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this community service activity is to improve the fastcounting ability of SMK students and the team can also increase the empowerment of partners according to the problems faced and can establish cooperation with partners. The activity took place on May 20, 2024 at SMKN 2 Belu involving 50 SMK students. This Community Service (PkM) activity starts from situation analysis, activity design, socialization, implementation, and evaluation of activities. Some things that can be concluded are that students look enthusiastic and give the impression that this activity is very helpful in solving math problems, all students are involved in answering the questions given, and this method is not boring because there are chants and games played together. This activity was only limited to addition and multiplication material, and lasted for 1 day only so that not all students fully understood the material presented, this resulted in some students not meeting the KKM.